Influence of upper-limb muscle strength on the repeated change of direction ability in international-level wheelchair basketball players. Issue 4 (4th July 2022) - Iturricastillo, Aitor; Garcia-Tabar, Ibai; Reina, Raul; Garcia-Fresneda, Adrian; Carmona, Gerard; Perez-Tejero, Javier; Yanci, Javier
ABSTRACT: This study aims 1) to compare repeated change of direction ability (rCODA) and bench press (BP) between low (A category, ≤2.5) and high (B category, ≥3.0) sport classes and 2) to analyse the relationships between rCODA and BP performance in a sample of wheelchair basketball (WB) players. Seventeen world-class WB players volunteered participated in this study. All the players undertook two tests: the repeated (x12) Modified Agility T-test (rMAT) to measure the rCODA and the movement velocity in a BP test. No significant differences were observed between categories in the rMAT and BP. For the total sample, BP variables with a mean propulsive velocity of 1 m·s −1 (V1LOAD ) largely correlated with all the full rMAT outcomes (r>-0.625; p < 0.05). Having a better BP could be favourable to perform repeated efforts and this seems particularly relevant in fatigue conditions, and especially for the B category players.